Translation Initiation Control by Heme-Regulated Eukaryotic Initiation Factor 2α Kinase in Erythroid Cells under Cytoplasmic Stresses - Linrong Lu; Anping Han; Jane-Jane Chen (2001)
AbstractCytoplasmic stresses, including heat shock, osmotic stress, and oxidative stress, cause rapid inhibition of protein synthesis in cells through phosphorylation of eukaryotic initiation factor 2α (eIF2α) by eIF2α kinases. We have investigated the role of heme-regulated inhibitor (HRI), a heme-regulated eIF2α kinase, in stress responses of erythroid cells. We have demonstrated that HRI in reticulocytes and fetal liver nucleated erythroid progenitors is activated by oxidative stress induced by arsenite, heat shock, and osmotic stress but not by endoplasmic reticulum stress or nutrient starvation. While autophosphorylation is essential for the activation of HRI, the phosphorylation status of HRI activated by different stresses is different. The contributions of HRI in various stress responses were assessed with the aid of HRI-null reticulocytes and fetal liver erythroid cells. HRI is the only eIF2α kinase activated by arsenite in erythroid cells, since HRI-null cells do not induce eIF2α phosphorylation upon arsenite treatment. HRI is also the major eIF2α kinase responsible for the increased eIF2α phosphorylation upon heat shock in erythroid cells. Activation of HRI by these stresses is independent of heme and requires the presence of intact cells. Both hsp90 and hsc70 are necessary for all stress-induced HRI activation. However, reactive oxygen species are involved only in HRI activation by arsenite. Our results provide evidence for a novel function of HRI in stress responses other than heme deficiency. ACKNOWLEDGMENTThis work was supported by Public Health Service grant DK-16272 to J.-J.C. from the National Institute of Diabetes and Digestive and Kidney Diseases.